2003
DOI: 10.1021/om034218g
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of Cyclooctadiene Ligands in Iridium Chemistry and Catalysis

Abstract: In the presence of reactants such as acetonitrile, trimethylphosphine, and diphenylacetylene, the 1,5-cyclooctadiene iridium(I) complex [Ir(1,2,5,6-η-C 8 H 12 )(NCCH 3 )(PMe 3 )]BF 4 (1) has been found to transform into compounds containing cyclooctadiene or cyclooctadienyl ligands in η 3 ,η 2 -; κ,η 3 -; κ 2 ,η 2 -; and η 3 -coordination modes. All these reactions are initiated by an intramolecular C-H activation of the COD ligand and followed by either inter-or intramolecular insertion, or reductive eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 30 publications
3
72
0
1
Order By: Relevance
“…Similar principles could apply to Si À Si bond formation mediated by late transition metals but again lack mechanistic support. [112][113][114] In 1992, Tilley et al had already suggested that "a transient intermediate which may form prior to a four-center transition state is a complex with coordinated SiÀH, HÀH, or Si À Si s bonds." [115] There are now a few examples of C À C agostic complexes, [65,[116][117][118][119][120] but intermolecular s-C À C complexes are not known as far as we are aware.…”
Section: Methodsmentioning
confidence: 99%
“…Similar principles could apply to Si À Si bond formation mediated by late transition metals but again lack mechanistic support. [112][113][114] In 1992, Tilley et al had already suggested that "a transient intermediate which may form prior to a four-center transition state is a complex with coordinated SiÀH, HÀH, or Si À Si s bonds." [115] There are now a few examples of C À C agostic complexes, [65,[116][117][118][119][120] but intermolecular s-C À C complexes are not known as far as we are aware.…”
Section: Methodsmentioning
confidence: 99%
“…When using DCE as the solvent, addition of fluorinated co-solvents was necessary to retain high yields and reaction rates (not shown). [20] Importantly, nonchlorinated solvents, such as 2-Me-THF (with or without TFE added) and propylene carbonate (PC), [21] also allowed for efficient catalysis (Table 1, entries [11][12][13].…”
mentioning
confidence: 99%
“…While 5 is stable under CO atmosphere, removal of solvent and addition of CD 2 Cl 2 results in retro-cyclometalation and predominately a mixture of 2 55 and 6 (no 5 observed after 12 h) -the later formed by reaction of 2 with liberated CO. To help gain insight into the mechanism of the cyclometalation 60 reaction, we targeted the reaction of 2 with diphenylacetylene, as an external hydride acceptor. This alkyne has previously been used to trap out C-H bond activation reactions of COD coordinated to iridium 10 and we wished to explore if such reactivity was important in our system. Heating 2 with a large 65 excess of diphenylacetylene at 318 K resulted in the gradual, but irreversible, formation of the new cyclometalated complex [Ir(COD)(py-I t Bu'){κ 1 -C(Ph)=CHPh}][BAr F 4 ] 7, which was isolated in 61% yield after 11 days (Scheme 3).…”
mentioning
confidence: 99%